2018
DOI: 10.1002/cam4.1466
|View full text |Cite
|
Sign up to set email alerts
|

Living on a farm, contact with farm animals and pets, and childhood acute lymphoblastic leukemia: pooled and meta‐analyses from the Childhood Leukemia International Consortium

Abstract: The associations between childhood acute lymphoblastic leukemia (ALL) and several factors related to early stimulation of the immune system, that is, farm residence and regular contacts with farm animals (livestock, poultry) or pets in early childhood, were investigated using data from 13 case–control studies participating in the Childhood Leukemia International Consortium. The sample included 7847 ALL cases and 11,667 controls aged 1–14 years. In all studies, the data were obtained from case and control paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(71 reference statements)
0
15
0
1
Order By: Relevance
“…Finally, having pets at home has been suggested to be a protective factor for non-communicable diseases in children and adults ( Table 15 ). Specifically, being exposed to pets in the first year of life was found to reduce the risk of acute lymphoblastic leukemia [ 110 ]. For adults, being exposed to a pet was suggested to reduce Crohn’s disease and ulcerative colitis [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, having pets at home has been suggested to be a protective factor for non-communicable diseases in children and adults ( Table 15 ). Specifically, being exposed to pets in the first year of life was found to reduce the risk of acute lymphoblastic leukemia [ 110 ]. For adults, being exposed to a pet was suggested to reduce Crohn’s disease and ulcerative colitis [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular Switzerland has one of the highest livestock densities in Europe, with around 1.71 livestock units per hectares of utilized agricultural area in 2010 [44]. Previous studies have found a reduced risk of childhood ALL and lymphoma among children with early life exposure to farm animals [45][46][47], while increased risks were found for other cancer subtypes, such as AML, CNST, germ-cell tumours and astrocytoma [18,47]. Given that about 80% of parents with high likelihood of exposure category belonged to job category "market-oriented crop and animal producers" (S1), it is possible that our analysis was confounded by exposure to farm animals.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for this hypothesis stems from a recent large-scale pooled and meta-analysis of 7847 leukemia cases (immunophenotype: 76% B-lineage, 10% T-ALL, rest unspecified/unknown) and 11 667 controls by the Childhood Leukemia International Consortium. 47 The consortium demonstrated that regular contact with livestock, poultry, and pets in infancy (<1 year of age) reduced the risk of ALL development significantly. 47 The reduced risk associated with contact with livestock was remarkably clear (odds ratio = 0.65; 95% confidence interval, 0.50-0.85).…”
Section: Evidence For Training Of Immune Cells In Bcp-allmentioning
confidence: 99%